Effect of Filler Loading on the Tensile Properties of Multi-walled Carbon Nanotube and Graphene Nanopowder filled Epoxy Composites - Ervina, Junaidi; Mariattia, M.; Sinin, Hamdan (Elsevier B.V., 2016)
At present, carbon nanotube (CNT) and graphene are attracting a great deal of attention due to their superior structural and functional properties as well as its suitability for engineering applications. In this work, multi-walled carbon nanotube (MWCNT) and graphene nanopowders (GNP) filled epoxy composites were fabricated via ultrasonication and casting method. The effect of MWCNT and GNP loadings (0-1 vol%) on tensile properties of filled epoxy composites were investigated. The experimental results prove that the strength and modulus of filler (MWCNT and GNP) filled epoxy composites are lower as compared to pristine epoxy. However, the addition of GNP at 0.8 vol% had slightly increased the composite tensile modulus which was approximately 3.4% in comparison with pristine epoxy. Thus, in general it indicates that the addition of filler (MWCNT and GNP) had reduced the mechanical properties of epoxy composites. The reason for this is due to the high aspect ratio and high van der Waals attraction of the MWCNT causes entanglement among nanotube. Subsequently, this leads to aggregations and agglomerations which limit the load transfer from the matrix to nanotubes. Similarly, agglomeration in GNP composites is due to the stacking of flaky-shaped GNP particles and the sharp edges of GNP cause cracks to initiate and resulting in lower mechanical properties.